Gestão escolar : a prática pedagógica administrativa na política de educação inclusiva - Tezani, Thaís Cristina Rodrigues (2008)
This thesis is addressing the analysis of knowledge involving the practice of teaching and administrative daily school administrators who work with the proposed construction of a municipal system of inclusive education, while public educational policy. There was a kind of ethnographic qualitative research applied to education, guided by the question: "What are the knowledge and who subsidize the administrative practice and teaching of school management before the construction of the inclusive school?". The specific objectives of the research were: track the trajectory of the school management before the draft inclusive education in three schools from elementary schools to midsize a city of the state of Sao Paulo, which has adopted as public policy the construction of a municipal system City of inclusive education. The schools selected were the oldest, an intermediate-old and a newly inaugurated; identify the theoretical and philosophical assumptions of administrative practice and teaching of daily school manager and his role in front of building inclusive school. As stages of work, include: 1) literature review of: a) the qualitative research Ethnographic type applied to education, b) principles of autonomy, planning, decentralization, c) training of school manager and d) relationship between school management and construction of inclusive school, 2) data collection in schools; 3)description and categorization of data collected and 4) analysis and interpretation of results. For the development of methodology, were used observations of the participants, semi-structured interviews, analysis of official documents from the school, pictures of physical space. It follows that there is a lack of political-educational project built collectively, difficulty in developing coordinated actions and adapted to the existing problems of interpersonal relationships; a huge gap between policy proposal, the political discourse preached and performed daily pedagogical practice. The school management is, yes, one responsible for building the inclusive school, but its practice is directed to administrative issues in the educational expense.